Polychlorinated Biphenyls (PCBs) and Cognitive Deficits - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1990)
The effects of prenatal exposure to polychlorinated biphenyls (PCBs) and related contaminants on the CNS function of infants born to women who had consumed Lake Michigan sports fish have been investigated in 236 children previously evaluated for PCB-related deficits in infancy and reassessed at four years of age in the Psychology Department, Wayne State University, Detroit, MI and the Michigan Department of Public Health, Lansing, MI.